THE IMPACT OF USING A CLASS SCHEDULE FOR PROGRAMMING THERMOSTATS ON THE ENERGY CONSUMPTION OF A SCHOOL BUILDING - ДЕШКО, В. І.; ГОЛУБЕНКО, О. О. (Technologies and Engineering, 2024)
Introduction. Variations in temperature reduction during periods of building inactivity have proven to be an effective energy-saving measure. However, there is still potential for energy savings in the field of thermal regulation, specifically related to more detailed heating schedules. Investigating the advantages and disadvantages of detailed heating schedules for thermostat programming becomes an important direction in the development of modern heating and conditioning systems. Purpose. The objective of this study is to explore the advantages and disadvantages of implementing a heating schedule based on the school class schedule for the heating system. Methodology. The research is conducted based on energy modeling using the DesignBuilder software environment. Findings. The results of the energy modeling of the building included an examination of the impact of implementing a heating schedule based on the school class schedule for buildings with different levels of thermal insulation. The class schedule-based heating schedule demonstrated several advantages over a simpler schedule with gaps during non-working hours, including over 3% higher energy efficiency and a 3.3–3.7% reduction in peak heating system loads. Scientific novelty. The study investigates the impact of implementing a class schedule-based heating schedule on the energy efficiency of a school building and the comfort of occupants. Practical value. Considering climate and building characteristics, as well as mitigating the human factor's influence through the use of programmable thermostats, can contribute to the development of effective heating management strategies, leading to significant energy resource savings.